Melting control of phase change material of semi-cylinders inside a horizontal baffled channel: Convective laminar fluid–structure interaction. (February 2023) - Salih, Salah M.; Alsabery, Ammar I.; Hussein, Ahmed K.; Ismael, Muneer A.; Ghalambaz, Mohammad; Hashim, Ishak
Abstract: The problem studied in this paper consists of forced fluid flow inside a horizontal channel involving two semi-cylinders and two flexible baffles attached alternatively to the lower and upper walls of the channel. A phase change material fills the semi-cylinders, which are being heated by constant temperature. Cold air is forced through the channel to induce the contributions of convective and conductive heat transfers, fluid–structure interaction and the melting of phase change material. The prevailing mathematical equations of these physics are normalized and solved using the finite element method with the ALE scheme. The influential parameters are: dimensionless time τ, the elasticity modulus of the baffles E and the Reynolds number R e . The most important results show a retardation of melting volume fraction with increasing Reynolds number and decreasing the elasticity modulus of the flexible baffles. It is found that elevating R e from 10 to 500 and E from 5 × 1 0 4 to 5 × 1 0 6, the melting volume fraction MVF at τ = 15 reduces by 4.15% and increases by 5.2%, respectively. The flexible baffles having a lower modulus of elasticity augment the Nusselt number very slightly (0.9%), while the pressure drop along the channel decreases notably. Highlights: Transient forced convective with Fluid–structure interaction does being investigated. Horizontal channel with two alternative PCMs and flexible baffles are applied. Galerkin finite element approach and ALE technique are employed. It is noticed that the baffles deflect excessively at very low Reynolds.